Fine-scale genetic structure and wolbachia infection of aedes albopictus (Diptera: Culicidae) in Nanjing city, China - Zhang, Heng-Duan; Gao, Jian; Xing, Dan; Guo, Xiao-Xia; Li, Chun-Xiao; Dong, Yan-De; Zheng, Zhong; Ma, Zu; Wu, Zhi-Ming; Zhu, Xiao-Juan; Zhao, Ming-Hui; Liu, Qin-Mei; et al. (Frontiers in Genetics, 2022)
Aedes albopictus is an indigenous primary vector of dengue and Zika viruses in China, little is known about its variation at the microspatial level, which is essential for its management. Thus, the present study examines how the Ae. albopictus population varies and disperses among microspatial regions of Nanjing City. The genetic structure of 17 Ae. albopictus populations collected from different regions of Nanjing City was investigated based on 9 microsatellite loci and the mitochondrial coxI gene. Meanwhile, the Wolbachia infection status of each population was also assessed with Wolbachia-specific premiers. The urban area populations (7.353 ± 4.975) showed a lower mean na value than the urban fringe region populations (7.866 ± 5.010). A total of 19 coxI haplotypes were observed among all individuals via haplotype genotyping, with the highest diversity observed among the urban fringe Ae. albopictus populations (Hd = 0.456) and the lowest among the urban populations (Hd = 0.277). Each Ae. albopictus population showed significant departure from HWE, and significant population expansion was observed in only three populations from the urban (ZSL), urban fringe (HAJY), and rural areas (HSZY) (P < 0.05). Combined with DAPC analysis, all the Ae. albopictus populations were adequately allocated to two clades. AMOVA results showed that most (96.18%) of the genetic variation detected within individuals (FIT = 0.22238, P < 0.0001), while no significant positive correlation was observed via isolation by distance (IBD) analysis (R2 = 0.03262, p = 0.584). The TCS network of all haplotypes showed that haplotype 1 (H1) and haplotype 4 (H4) were the most frequent haplotypes among all populations, and the haplotype frequency significantly increased from urban regions (36.84%) to rural regions (68.42%). Four direct migration routes were observed among Ae. albopictus populations between rural and urban regions. Furthermore, Wolbachia genotyping results showed that most of the individuals of each population were coinfected with Wolbachia A and Wolbachia B. The independent infection rate of Wolbachia A was slightly higher than that of Wolbachia B, and no significant differences were observed among different regions. Our findings may provide a solid foundation for the scientific prevention and control of Ae. albopictus.